Pneumatic Coiling Actuator Inspired by the Awns of Erodium cicutarium - Geer, Ryan; Iannucci, Steven; Li, Suyi (Frontiers in Robotics and AI, 2020)
This study examines the coiling and uncoiling motions of a soft pneumatic actuator inspired by the awn tissue of {\it Erodium cicutarium}. These tissues have embedded cellulose fibers distributed in a {\it tilted} helical pattern, which induces hygroscopic coiling and uncoiling in response to the daily changes in ambient humidity. Such sophisticated motions can eventually ``drill'' the seed at the tip of awn tissue into the soil: a drill bit in the plant kingdom. Through finite element simulation and experimental testing, this study examines a soft pneumatic actuator that has a similar reinforcing fiber layout to the Erodium plant tissue. This actuator, in essence, is a thin-walled elastomeric cylinder covered by tilted helical Kevlar fibers. Upon internal pressurization, it can exhibit a coiling motion by a combination of simultaneous twisting, bending, and extension. Parametric analyses show that the coiling motion characteristics are directly related to the geometry of tilted helical fibers. Notably, a moderate tilt in the reinforcing helical fiber leads to many coils of small radius, while a significant tilt gives fewer coils of larger radius. The results of this study can offer guidelines for constructing plant-inspired robotic manipulators that can achieve complicated motions with simple designs.